EFFECT OF DEPURATION ON INDIAN COCKLE ANADARA GRANOSA - Chakrabarti, R; Khasim, D Imam (Indian Journal of Fisheries, 2011)
Anadara granosa (Linna’ us) has a wide distribution along Kakinada coast. Its commercial value as exportitem is being explored. 1.5 to 2%0 salinity was sufficient for survival of live cockle. Change in compositionin each component in cockle during depuration was also studied. By removal of mantles and gills fromsteamed whole meat, acid insoluble ash content of meat can be reduced considerably. Moreover pepsindigestibility can be incNased to 87.8%. Not much effect of chlorination during depuration was noticed